Safety and efficacy of simultaneous photorefractive keratectomy and corneal cross-linking in managing suspected keratoconus - Ali Dal; Mehmet Canleblebici; Murat Erdağ (Indian Journal of Ophthalmology)
Purpose: To evaluate the safety and efficacy of combining photorefractive keratectomy (PRK) and corneal cross-linking (CXL) in patients with suspected keratoconus. Methods: This retrospective, non-randomized study included patients who underwent simultaneous PRK and CXL between March 2020 and March 2023. Patients were divided into two groups: group 1 (PRK only without keratoconus) and group 2 (PRK + CXL with suspected keratoconus). Eligibility criteria included stable refractive error for at least 1 year, spherical equivalent refractive error not exceeding −4.0 D, and central corneal thickness between 470 and 500 µm. Exclusion criteria included corneal ectasia, previous ocular surgeries, systemic diseases, and pregnancy. Preoperative and postoperative assessments included uncorrected distance visual acuity (UCVA), best-corrected visual acuity (BCVA), spherical equivalent, corneal topography, and endothelial cell count. Results: The study included 98 eyes from 98 patients, with 47 eyes in group 1 and 51 eyes in group 2. Significant improvements in UCVA and BCVA were observed in both groups 12 months postoperatively (P < 0.001). Similar reductions in cycloplegic spherical and cylindrical refraction values were observed in both groups (P < 0.01). No cases of corneal ectasia were reported. Grade 1 corneal haze was observed in 8.5% of eyes in group 1 and 9.8% of eyes in group 2, all of which resolved within the 12-month follow-up period. Conclusion: The combination of PRK and CXL is a safe and effective treatment option for patients with suspected keratoconus, providing significant improvements in visual acuity and refractive stability without increasing the risk of corneal ectasia.